Modelling the Halal-Wellness Nexus: A Strategic Evaluation of Destination Competitiveness through Penta-Helix Collaboration in West Java - Suryana, Marceilla; Barusman, Andala Rama Putra; Indriani, Novita (Journal of Consumer Studies and Applied Marketing, 2025)
The post-pandemic global tourism landscape has experienced a paradigm shift toward health-oriented travel, positioning the halal-wellness nexus as a critical driver of destination competitiveness. Despite possessing world-class geothermal resources and profound indigenous healing traditions, West Java's wellness tourism sector remains constrained by fragmented regional branding and infrastructure bottlenecks. This study quantitatively evaluates West Java's strategic market posture to bridge the gap between latent destination potential and actionable marketing execution. Utilizing a quantitative descriptive design, the research employs the Internal Strategic Factors Analysis Summary (IFAS) and External Strategic Factors Analysis Summary (EFAS) matrices through structured expert consultations involving a panel of 15 purposively selected Penta-Helix stakeholders. These experts comprise representatives from academia, government (Disbudpar), industry (spa/resort operators), community leaders, and tourism media. The findings reveal equivalent IFAS and EFAS scores of 2.77, mapping the destination into Cell V (Hold and Maintain) of the Internal-External Matrix. This positioning indicates a stable yet under-optimized ecosystem that must transition toward an aggressive growth posture. Through a consensus-driven process linking macro-environmental factors to granular interventions, the study formulates a strategic TOWS mix centred on a "Heritage-Health-Harmony" brand architecture. Actionable recommendations from the expert panel include integrating Mega Mendung batik motifs into the destination’s visual identity, optimising tourist buses for regional wellness corridors, and facilitating interest-free financing schemes to elevate local hospitality standards ethically. This framework provides a data-driven blueprint for policymakers to transform West Java into a resilient, globally competitive halal-wellness hub.